associated stroke in a 3-year-old girl - Gun-Ha Kim; Won Hee Seo; Bo-Kyung Je; So-Hee Eun (Korean Pediatric Society, 2013)
Infectious diseases precede a significant proportion of acute ischemic strokes in children. Here, we report a case of acute ischemic stroke in a 3-year-old girl with a Mycoplasma pneumonia-associated respiratory tract infection. She developed an acquired prothrombotic state of protein S deficiency and had increased fibrinogen and fibrinogen degradation product levels and increased titer of antinuclear antibodies. However, these conditions were completely alleviated at the 1-month follow-up examination. Infection with M. pneumoniae may cause a transient prothrombotic state that can potentially cause a thrombus.